The Role of Paraphrasing in Writing Research Papers - Pungky Ramadhani (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
Almost all people in this world have experienced in writing a research paper. Nevertheless, there are only some people who understand how to write appropriately. Plagiarism still becomes a big problem among the writers. This happens because they often get difficulty in integrating sources into the text. As the writers, they should know how to overcome that problem. The existence of paraphrasing can be a way to avoid the plagiarism. The writers can paraphrase a direct quote of someone using their own words. This can be a great way to increase the quality of research papers.